Associations between declines in uneven terrain walking speed and visuospatial working memory in older adults - Hwang, Jungyun; Liu, Chang; Winesett, Steven P.; Fettow, Tyler; Shah, Valay A.; Chatterjee, Sudeshna A.; Manini, Todd M.; Hass, Chris J.; Seidler, Rachael D.; Ferris, Daniel P.; Roy, Arkaprava; Reuter-Lorenz, Patricia A.; et al. (Frontiers in Aging Neuroscience, 2026)
IntroductionMobility and cognitive functions often decline concurrently in older adults, and may be particularly detrimental to walking in complex environments such as uneven terrain. Walking on uneven terrain particularly relies on visuospatial working memory to continuously adjust gait patterns; however, this relationship remains understudied. The objectives of this study are to examine group differences in uneven terrain walking speed and visuospatial n-back task performance across varying task demands among younger adults, and among older adults with high and low physical function and to assess whether uneven terrain-induced reductions in walking speed are associated with declines in n-back performance, particularly among low-functioning older adults. As an exploratory aim, we also examined age-related differences in brain activity during n-back performance to provide additional context for interpreting neural responses across tasks.MethodsThe analysis included 24 younger adults (aged 22.8 ± 3.3) and 44 older adults (aged 74.0 ± 5.6). Using the Short Physical Performance Battery (SPPB), older adults were categorized into high physical function (n = 29) and low physical function (n = 15), with scores below 10 indicating a lower level of physical function. Uneven terrain walking speed was measured as participants traversed four novel custom-made overground surfaces: flat, low, medium, and high terrain unevenness. Visuospatial walking memory was assessed on a spatial n-back task that included four n-back levels, ranging from 0-back to 3-back. Prefrontal cortical activity was measured using functional near-infrared spectroscopy (fNIRS) while participants performed the n-back task.ResultsCompared to younger adults, older adults exhibited poorer working memory performance and slower uneven terrain walking speeds, with both effects being particularly pronounced in low functioning older adults. Slower walking speeds as terrain became more uneven were associated with poorer n-back performance as n-back level increased, with a larger effect size observed in the low physical functioning older adults. fNIRS results revealed comparable levels of prefrontal cortical activity between younger and older groups during the n-back tasks. Prefrontal cortical activity did not increase with higher task demands (i.e., increasing n-back levels) in any of the groups.ConclusionThese findings support a relationship between declines in uneven terrain mobility and n-back cognitive function in older adults; however, this relationship was not observed in younger adults. Further research is needed to understand the shared neural mechanisms underlying age-related declines in mobility and cognitive function.